Émilie du Châtelet and the foundations of physical science - Brading, Katherine, 1970- author.
1 online resource.
Keywords: The influence of Foundations of Physics (also called Institutions de physique), published in Paris in 1740, written by Gabrielle Emilie Le Tonnelier de Breteuil Du Châtelet (or Emilie Du Châtelet (1706-1749)).